Analysis Index of Retained Strenght on AC-WC Asphalt Mixture with the Addition of Cigarette Filter Waste as an Alternative for Asphalt Modification - Arifudin, Rahmat; Pristyawati, Tantin; Ristanto, Iwan (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
In order to provide an alternative asphalt mixture that is more durable, various efforts have been made to improve the quality of asphalt, therefore research is needed on polymer modified asphalt by replacing some of the asphalt with cigarette filter waste. In this study, cigarette filter waste was substituted into asphalt with proportions of 2%, 5%, and 8%. The purpose of this study was to determine the percentage of cigarette filter waste that affects the AC-WC mixture based on marshall characteristics and residual stability. The optimum asphalt content (KAO) used was 5.1%, with the results showing that the addition of cigarette filter waste affected the marshall characteristic values, namely the specific gravity value, Voids Filled with Asphalt (VFA), and the highest stability was at a variation of 2%, while the Voids in Mix (VIM), Void in Mineral Aggregate (VMA), and the highest flow. were at a variation of 8%. The residual stability index test showed that water affected the durability of the AC-WC mixture, as evidenced by the highest value in the 24-hour immersion variation with a cigarette filter content of 2% which decreased with increasing immersion time. The addition of cigarette filter waste into the AC-WC mixture has met the Bina Marga Specifications in the Marshall characteristic test, but the change in the residual stability index was only at a soaking time of 24 hours, while for other periods it did not comply with the Bina Marga specifications.